SYNTHESIS AND STUDY OF THE PROPERTIES OF COMPOUNDS OF N-ACYLAMINOACIDS WITH METALS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the work of compounds of the N-acylaminoacids with metals (Co, Mg, Ni, Mn, Zn) were synthesized. The compounds were isolated in solid state, elemental composition and physical-chemical properties were determined.
Keywords: α-aminoacids, N-acylaminoacids , higher carboxylic acids, IR-spectroscopy.